2019
DOI: 10.1177/0022219419881646
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of Elementary Mathematics Interventions: Comparisons of Students With Mathematics Difficulty With and Without Comorbid Reading Difficulty

Abstract: In this synthesis, we reviewed 65 studies involving elementary students (i.e., grades 1–5) identified with mathematics difficulty (MD) in which authors implemented a mathematics intervention. Of these studies, we identified 33 group designs, 9 quasi-experimental designs, and 23 single-case designs. We aimed to synthesize performance differences between students with MD with and without reading difficulty (RD). We identified three categories of students for analysis: Students with MD+RD, MD-alone, or MD-nonspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 105 publications
0
25
0
1
Order By: Relevance
“…Students with MD display challenges with recalling mathematical facts, performing calculations, and applying mathematical reasoning, leading to low mathematics achievement (Powell et al, 2020). These challenges may be connected to a variety of cognitive factors, including verbal comprehension, working memory, and processing speed (Peterson et al, 2017; Willcutt et al, 2013), as well as mathematical factors, such as number sense (Slot et al, 2016), counting (Aunio et al, 2015), comparison (Toll & Van Luit, 2014), and mathematical language (Toll & Van Luit, 2014).…”
Section: Students With Mathematics Difficultiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Students with MD display challenges with recalling mathematical facts, performing calculations, and applying mathematical reasoning, leading to low mathematics achievement (Powell et al, 2020). These challenges may be connected to a variety of cognitive factors, including verbal comprehension, working memory, and processing speed (Peterson et al, 2017; Willcutt et al, 2013), as well as mathematical factors, such as number sense (Slot et al, 2016), counting (Aunio et al, 2015), comparison (Toll & Van Luit, 2014), and mathematical language (Toll & Van Luit, 2014).…”
Section: Students With Mathematics Difficultiesmentioning
confidence: 99%
“…These challenges may be connected to a variety of cognitive factors, including verbal comprehension, working memory, and processing speed (Peterson et al, 2017; Willcutt et al, 2013), as well as mathematical factors, such as number sense (Slot et al, 2016), counting (Aunio et al, 2015), comparison (Toll & Van Luit, 2014), and mathematical language (Toll & Van Luit, 2014). As a result, students with MD typically score lower on measures of the WPS performance than their peers without MD (Powell et al, 2020).…”
Section: Students With Mathematics Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis on the phonological pathway may elicit the consideration of incorporating literacy contents in classroom instruction and interventions focusing on numeracy materials. Some reports have suggested that children with single or comorbid difficulties in reading and/or math could benefit from some forms of combined reading and math remediations (e.g., Fuchs et al, 2012 ; Glenberg et al, 2012 ; Powell et al, 2020 ).…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…Also important for transfer is contextual variation in which students solve standard and nonstandard problems with similar underlying conceptual structures to improve more abstract mathematical reasoning, such as relational understanding of the equal sign (e.g. 4 + x = 7 vs. 7 = x + 4) (Powell et al, 2020). For children who do not respond to the combination of high-quality…”
Section: Small Group Interventionsmentioning
confidence: 99%